ETHNOPHARMACOLOGICAL STUDY IN FAITH HEALERS OF COLINA DO HORTO, IN JUAZEIRO DO NORTE-CE, BRAZIL - Lima, Wenderson Pinheiro de; Gomes Filho, Antoniel dos Santos; Ifadireó, Miguel Melo; Bitu, Vanessa de Carvalho Nilo (Científic@ - Multidisciplinary Journal, 2019)
Much of our information and knowledge today is derived from popular culture, including the use of medicines to treat diseases that affect humankind. Ethnopharmacological research allows the knowledge of traditional communities to contribute to scientific studies and vice versa, since it involves not only botanical and pharmaceutical knowledge but also anthropology aspects. Throughout the Ceará Cariri region, the use of natural resources in traditional healing methods is very evident. Accordingly, the aim of this study was to investigate the popular knowledge about the therapeutic use of natural resources by faith healers in Colina do Horto in Juazeiro do Norte, CE, Brazil. Informants who were self-proclaimed prayer people and faith healers, of both sexes, were subjected to semi-structured interviews consisting of guiding questions, which allowed us to achieve the proposed objectives. The data collected were related to the origin of the resources used in magical-religious procedures, part used, method of preparation, required amount, indications for use and contraindications. Analysis of data allowed the tabulation of the species so as to correlate all the variables studied. In addition, informant consensus factor and relative importance were determined. The informants had an average age of 66 years, and the majority were elderly, illiterate and female. Among the six species used in the healing procedures, the most prevalent was Jatropha gossypiifolia. Of the 53 species cited as complementary for healing, those especially used belonged to the families Lamiaceae and Asteraceae.